The Effectiveness of Fluoroscopically Guided Cervical Transforaminal Epidural Steroid Injection for the Treatment of Radicular Pain; a Systematic Review and Meta-analysis. Issue 1 (10th June 2019) - Conger, Aaron; Cushman, Daniel M; Speckman, Rebecca A; Burnham, Taylor; Teramoto, Masaru; McCormick, Zachary L
Abstract: Objective: Determine the effectiveness of fluoroscopically guided cervical transforaminal epidural steroid injection (CTFESI) for the treatment of radicular pain. Design: Systematic review and meta-analysis. Subjects: Persons aged ≥18 years with cervical radicular pain due to disc herniation or degenerative spondylosis. Comparison: Sham, placebo procedure, or active standard of care treatment, excluding alternative versions of epidural steroid injection. Outcomes: The primary outcome measure was patient-reported improvement in pain of at least 50% from baseline, assessed four or more weeks after the treatment intervention. Secondary outcomes included validated functional assessment tools and avoidance of spinal surgery. Methods: Randomized or nonrandomized comparative studies and nonrandomized studies without internal control were included. Three reviewers independently assessed publications in the Medline, PubMed, and Cochrane databases up to July 2018. The Grades of Recommendation, Assessment, Development and Evaluation (GRADE) system was used to evaluate risk of bias and overall quality of evidence. A meta-analysis was conducted for comparative measures of effect and for within-group response rates if applicable. Results: There were no studies with an internal comparison group (control group) meeting the review's definition of comparison group. Therefore, comparative measures of effect were not calculated. In cohort studies, pooled response rates were 48% (95% confidence interval [CI] = 34–61%) at one month and 55% (95% CI = 45–64%) at three months. Conclusions: Approximately 50% of patients experience ≥50% pain reduction at short- and intermediate-term follow-up after CTFESI. However, the literature is very low quality according the GRADE criteria, primarily due to a lack of studies with placebo/sham or active standard of care control comparison groups.